METAFORA KASTIL JEPANG DENGAN SIFAT MENUMPUK ALA LEGO PADA PERANCANGAN PUSAT KOMUNITAS JEPANG DI SOLO RAYA, JAWA TENGAH - Muhamad Dirham Okta Raizal; Hardiyati Hardiyati; Maya Andria Nirawati (ARSITEKTURA, 2017)
This journal was done in the interest of architectural studies. The goal of the research was to build a Japanese Community Center in Solo. The study began from a certain phenomenon. Ever since the signing of Peace Treaty between Indonesia and Japan, both country had immersed themselves in various cultural exchanges. This leads to the increase of Japanese culture lovers in Indonesia almost every year. To anticipate and control this phenomenon, a place that can hold and regulate the speed and effects of it is needed. The Japan Community Centre will be a place for Japanese Communities’s activities, a medium for learning Japanese culture, and the new spot of historical vacation for Solo City. Metaphorical Architecture was chosen as the design approach with consideration that through Metaphorical Architecture, the character and purpose of the building can be better presented for the public. The Metaphorical Architecture used was the mix of Abstract Metaphor (intangible) and Concrete Metaphor (tangible). The main problem of this designing process is what will be metaphored through this Japan Community Centre. The exploration starts from chosing the name for the building, which is Mugen Jou (Infinity Castle). The metaphorical charcteristics that will be used, based on the name chosen, are Grand, Firm, Massive, The feel of Japanese Castle, Uncountable visualization, and Stacked ala Lego.Keywords: Metaphorical, Grand, Firm, Massive, Castle, Uncountable